Targeting Strategies for Enhancing Paclitaxel Specificity in Chemotherapy - Ma, Yuan; Yu, Sifan; Ni, Shuaijian; Zhang, Baoxian; Kung, Angela Chun Fai; Gao, Jin; Lu, Aiping; Zhang, Ge (Frontiers in Cell and Developmental Biology, 2021)
Paclitaxel (PTX) has been used for cancer treatment for decades and has become one of the most successful chemotherapeutics in the clinic and financially. However, serious problems with its use still exist, owing to its poor solubility and non-selective toxicity. With respect to these issues, recent advances have addressed the water solubility and tumor specificity related to PTX application. Many measures have been proposed to remedy these limitations by enhancing tumor recognition via ligand-receptor-mediated targeting as well as other associated strategies. In this review, we investigated various kinds of ligands that have emerged as PTX tumor-targeting tools. In particular, this article highlights small molecule-, protein-, and aptamer-functionalized conjugates and nanoparticles (NPs), providing a promising approach for PTX-based individualized treatment prospects.